DOES APPLICATION OF NAPHTHENIC ACIDS IN EARLY FRUIT DEVELOPMENT STAGE RESULT IN PROLONGED EFFECT ON COLD STORAGE AND SHELF LIFE OF APRICOT FRUIT? - Kevrešan, Žarko; Milić, Biserka; Bajić, Aleksandra; Kovač, Renata; Milović, Maja; Kalajdžić, Jelena; Barać, Gordana (Food and Feed Research, 2022)
In this experiment, the effects of the application of naphthenic acids (NAs) on apricots in the early fruit development phases on fruit morphological properties, composition and postharvest properties were investigated. Two concentrations of NAs (1 mg/L and 3 mg/L) were applied at two development stages in the apricot cultivar NS-4. The application of NAs at the beginning of the petal fall development phase resulted in the reduction of fruit dimensions at harvest while the application 7 days later increased fruit dimensions. Although there were no significant differences in the most investigated characteristics between fruits treated with NAs and untreated control at harvest or in the postharvest period during 20 days of cold storage (1 ± 1 °C, RD 80%) and particularly after 3 days of shelf life at room temperature. However, compared to the untreated control, apricots treated with NAs were characterized by higher total soluble solids content accompanied by higher fructose content, and lower titratable acidity accompanied by higher succinic acid content. Apricots treated with NAs showed trends towards improved sensory properties: sweeter and less sour taste, with more expressed apricot aroma accompanied with decreased gumminess and crispiness and more intensive tissue breakdown, but without expressed notes of inappropriate taste.
Keywords: naphthenic acids; apricots; shelf life; postharvest; cold storage